The mediating role of speed in the global sourcing decision process. Issue 2 (March 2020) - Francioni, Barbara; Clark, Kevin D.
Abstract: The principal aim of this study is to provide theory and testing to elucidate the role of decision-maker's decision process and speed during the global sourcing decision-making process (GSDP). In order to achieve this goal, we examine the behavior of a sample of 202 decision-makers belonging to Italian SMEs in the manufacturing sector. Our main finding suggests that faster decisions during the GSDP process lead to superior financial and non-financial performance of the selected supplier. Moreover, we find support for dual processing theory wherein rationality and intuition of the GSDP are associated with increased supplier performance both directly and through their effects on decision speed. Results are discussed in terms of the GSDP, SME and strategic decision-making literatures and practical implications for managers in SMEs. Highlights: This study examines the role of decision-maker's decision process and speed during the global sourcing decision-making process (GSDP). We describe evidences from a quantitative study, that was conducted using 202 decision-makers belonging to Italian SMEs. We identify a link between speed and performance of the selected supplier. Rationality and intuition of the GSDP are associated with increased supplier performance both directly and indirectly.